Enhancing Front‐End Security: Protecting User Data and Privacy in Web Applications - Tkachenko, Oleksandr; Goncharov, Vadim; Jatkiewicz, Przemysław (Computer animation and virtual worlds, 2024)
ABSTRACT Conducting research on this subject remains relevant in light of the rapid development of technology and the emergence of new threats in cybersecurity, requiring constant updating of knowledge and protection methods. The purpose of the study is to identify effective front‐end security methods and technologies that help ensure the protection of user data and their privacy when using web applications or sites. A methodology that defines the steps and processes for effective front‐end security and user data protection is developed. The research identifies the primary security threats, including cross‐site scripting (XSS), cross‐site request forgery (CSRF), and SQL injections, and evaluates existing front‐end security methods such as Content Security Policy (CSP), HTTPS, authentication, and authorization mechanisms. The findings highlight the effectiveness of these measures in mitigating security risks, providing a clear assessment of their advantages and limitations. Key recommendations for developers include the integration of modern security protocols, regular updates, and comprehensive security training. This study offers practical insights to improve front‐end security and enhance user data protection in an evolving digital landscape. Comprehensive methods for protecting user data and privacy in web applications.